Towards a monitoring framework for securities financing transactions - Antoine Bouveret; Julien Jardelot; Joachim Keller; Philippe Molitor; John Theal; Mathieu Vital (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2013)
Supervisory authorities around the world are currently engaged in a policy debate over how to improve the information available on repurchase agreements (repos) and securities lending markets. Repo and securities lending transactions commonly referred to as securities financing transactions (SFTs), play a major role in the financial system. Although these can be relatively low-risk transactions by themselves, their pervasive use may give rise to systemic risk, as was observed during the recent financial crisis. In order to establish and implement a monitoring framework that allows for an effective assessment of the financial stability risks associated with SFTs, a number of considerable hurdles must be overcome and important decisions must be made. One contribution of this paper is to identify the potential obstacles and difficulties that may hinder the implementation of a monitoring framework in Europe.
Keywords: E44; G18; 330; securities lending; monitoring; securities financing transactions; systemic risk